Combination of Neuroprotective and Regenerative Agents for AGE-Induced Retinal Degeneration: In Vitro Study. (9th May 2017) - Bikbova, Guzel; Oshitari, Toshiyuki; Baba, Takayuki; Yamamoto, Shuichi
Abstract : To determine the most effective combination of neuroprotective and regenerative agents for cultured retinal neurons from advanced glycation end products- (AGEs-) induced degeneration, retinal explants of 7 adult Sprague-Dawley rats were three-dimensionally cultured in collagen gel and incubated in serum-free media and in 7 media; namely, AGEs, AGEs + 100  μ M citicoline, AGEs + 10 ng/mL NT-4, AGEs + 100  μ M TUDCA, AGEs + 100  μ M citicoline + TUDCA (doublet), and AGEs + 100  μ M citicoline + TUDCA + 10 ng/mL NT-4 (triplet) were examined. The number of regenerating neurites was counted after 7 days of culture, followed by performing TUNEL and DAPI staining. The ratio of TUNEL-positive cells to the number of DAPI-stained nuclei was calculated. Immunohistochemical examinations for the active form of caspase-9 and JNK were performed. All of the neuroprotectants increased the number of neurites and decreased the number of TUNEL-positive cells. However, the number of neurites was significantly higher, and the number of TUNEL-positive cells and caspase-9- and JNK-immunopositive cells was fewer in the retinas incubated with the combined three agents. Combination solutions containing citicoline, TUDCA, and NT-4 should be considered for neuroprotective and regenerative therapy for AGE-related retinal degeneration.